1986
DOI: 10.1542/peds.78.1.65
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Child Abuse and Neglect: A Randomized Trial of Nurse Home Visitation

Abstract: A program of prenatal and infancy home visitation by nurses was tested as a method of preventing a wide range of health and developmental problems in children born to primiparas who were either teenagers, unmarried, or of low socioeconomic status. Among the women at highest risk for care-giving dysfunction, those who were visited by a nurse had fewer instances of verified child abuse and neglect during the first 2 years of their children's lives (P = .07); they were observed in their homes to restrict and puni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
90
0
2

Year Published

1988
1988
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 777 publications
(92 citation statements)
references
References 0 publications
0
90
0
2
Order By: Relevance
“…[1][2][3] A subgroup analysis of poor unmarried teenage mothers in the first US trial (n=54) found verified maltreatment by age 2 years in 19% of 32 control children and 4% of the 22 children in the group in receipt of NFP during both pregnancy and infancy (mean % difference: 0.15, 95% CI −0.01 to 0.31). 1 Following up the same trial cohort, adjusted rates of verified state reports of child abuse and neglect perpetrated by mothers were lower in the group visited by nurses in pregnancy and infancy (0.29) when compared with the women in the control group (0.54) by 15 years (p<0.001). 4 Additionally, there was a 56% relative reduction in emergency department encounters for injuries and ingestions during the second year of life.…”
Section: Open Accessmentioning
confidence: 99%
“…[1][2][3] A subgroup analysis of poor unmarried teenage mothers in the first US trial (n=54) found verified maltreatment by age 2 years in 19% of 32 control children and 4% of the 22 children in the group in receipt of NFP during both pregnancy and infancy (mean % difference: 0.15, 95% CI −0.01 to 0.31). 1 Following up the same trial cohort, adjusted rates of verified state reports of child abuse and neglect perpetrated by mothers were lower in the group visited by nurses in pregnancy and infancy (0.29) when compared with the women in the control group (0.54) by 15 years (p<0.001). 4 Additionally, there was a 56% relative reduction in emergency department encounters for injuries and ingestions during the second year of life.…”
Section: Open Accessmentioning
confidence: 99%
“…Intervention strategies that have been shown effective in improving child outcomes could be drawn upon to help in developing prenatal programs (Daggett et al, 2000;Izard, 2002;Lutenbacher, 2001;Olds, Henderson, Kitzman, et al, 1998;Schaefer, 1991). For instance, Olds and colleagues found that pre-and postnatal home visitation services geared toward the prevention of child maltreatment have significant benefits both in the short-term reduction of negative parenting attitudes (Olds, Henderson, Tatelbaum, & Chamberlin, 1986) as well as in long-term reductions of child maltreatment (Olds, Henderson, Kitzman, et al, 1998) and of later juvenile delinquency (Olds, Henderson, Cole, et al, 1998). Given the strength of negative maternal preconceptions in longitudinally predicting child difficult temperament, less maternal sensitivity, and children's empathy, it seems imperative to develop strategies to ameliorate these preconceptions to provide more optimal opportunities and outcomes for children.…”
Section: Maternal Preconceptions About Parentingmentioning
confidence: 99%
“…Almost all of the primary prevention applications of this approach are implemented with high-risk families. Outstanding examples of this approach are David Olds' Prenatal/Early Infancy Project (Olds, Henderson, Chamberlin, & Tatelbaum, 1986) and Hawaii's Healthy Start program (Breaky & Pratt, 1991). While these programs vary greatly in terms of the type of home visitor used (e.g., nurses, nonprofessionals), program length, and the number of home visits, most begin prenatally or at birth and focus on the needs of the parent (usually the mother) and the parent-child relationship.…”
Section: Summary and Critique Parent Training Programs Havementioning
confidence: 99%